Antecedents and consequences of COVID-19 conspiracy beliefs: A systematic review. (May 2022) - van Mulukom, Valerie; Pummerer, Lotte J.; Alper, Sinan; Bai, Hui; Čavojová, Vladimíra; Farias, Jessica; Kay, Cameron S.; Lazarevic, Ljiljana B.; Lobato, Emilio J.C.; Marinthe, Gaëlle; Pavela Banai, Irena; Šrol, Jakub; et al.
Abstract: Rationale: Belief in COVID-19 conspiracy theories can have severe consequences; it is therefore crucial to understand this phenomenon, in its similarities with general conspiracy belief, but also in how it is context-dependent. Objective: The aim of this systematic review is to provide a comprehensive overview of the available research on COVID-19 conspiracy beliefs and to synthesise this research to make it widely accessible. Methods: We present a synthesis of COVID-19 conspiracy belief research from 85 international articles, identified and appraised through a systematic review, in line with contemporary protocols and guidelines for systematic reviews. Results: We identify a number of potential antecedents of COVID-19 conspiracy beliefs (individual differences, personality traits, demographic variables, attitudes, thinking styles and biases, group identity, trust in authorities, and social media use), their consequences (protective behaviours, self-centred and misguided behaviours such as hoarding and pseudoscientific health practices, vaccination intentions, psychological wellbeing, and other negative social consequences such as discrimination and violence), and the effect sizes of their relations with the conspiracy beliefs. Conclusions: We conclude that understanding both the potential antecedents and consequences of conspiracy beliefs and how they are context-dependent is highly important to tackle them, whether in the COVID-19 pandemic or future threats, such as that of climate change. Highlights: Belief in COVID-19 conspiracy theories can have severe consequences. This systematic review identifies potential antecedents and consequences of beliefs. Conspiracy belief consequences are context-dependent and time-sensitive. Understanding antecedents can help create interventions to decrease beliefs. This research provides insights for the COVID-19 pandemic but also for future threats.